Detoxifying processes during kanamycin-induced stress to Arabidopsis thaliana seedling growth. Issue 1 (1st January 2020) - Chen, Chen; Fu, Xiaoyan; Peng, Rihe; Tian, Yongsheng; Yao, Quanhong
Abstract: The increasing antibiotic application in agriculture has raised a potential risk to human health worldwide. Although high concentrations of antibiotics are lethal for plants without a resistant gene, it is not clear what detoxifying processes act in plants under low antibiotic concentration. Arabidopsis thaliana was selected to characterize the effects of kanamycin antibiotic toxicity on seedling growth in MS plates and pots, respectively. We investigated only control plants treated with kanamycin; but without comparison with transgenic ones, since we had no positive control transgenic plants. Gene expression profiles from plant material in pots were evaluated by customized oligonucleotide microarray. Morphological investigation indicated that kanamycin concentration is negatively correlated with A. thaliana seedling growth. Gene expression profile analysis detected that 542 and 116 genes were up- and down-regulated over five-fold in leaf tissue under the influence of kanamycin. The glutathione S-transferase and peroxidase gene families were involved in antioxidant defense mechanisms by preventing the accumulation of toxic products of reactive oxygen species (ROS). An exceeding amount of ROS after antibiotic-induced oxidative burst stimulated several over-presented processes for the balance between ROS and antioxidants. The significant increase in detoxification enzymes may indicate that efficient antioxidant machinery is the main method to ensure survival.